D0 meson production in high‐energy pp collisions based on dipole transverse momentum approach. Issue 1 (4th January 2023) - dos Santos, Gláuber S.; da Silveira, Gustavo Gil; Machado, Magno V. T.
Abstract: By employing the color dipole approach in the momentum representation taking into account the nonlinear behavior of the QCD dynamics, we make predictions for the D ‐meson differential cross‐section in terms of the transverse momentum and rapidity distributions considering pp collisions at the LHC. Moreover, a comparison between our results and the corresponding experimental measurements provided by the ALICE and LHCb experiments in different rapidity bins is performed.